The glitter end : a stationery shop mystery - Conroy, Vivian (Stationery shop mysteries, 2021)
"Delta Douglas is settling into small-town life in Tundish, Montana and her stationery shop is thriving. But when she asks well-known Montana artist Tilly Tay to display a miniature version of a mining town in her shop, trouble soon comes into the fold... Tilly is obsessed with getting everything just right before the unveiling, but when her grand reveal showcases a tiny murder, an element Tilly swears she did not add, confusion sweeps the crowd. And then a body is discovered perfectly mirroring Tilly's display, and townspeople are sure that life is imitating art. With the artist in custody and Delta's shop cast under a cloud of bad press, Delta and her faithful Paper Posse, along with Jonas and his canine sidekick Spud, must crack the case and save her store's reputation before it ends up in the shredder"--